STUDY OF PROBABILITY OF USING CIKARANG DRY PORT BASED ON PERCEPTION OF FREIGHT FORWARDERS - NURDIN EL HAKIM NIM : 24212301, LUKMAN
Major ports in Indonesia, particularly in Java are experiencing inefficiency problems that cause high logistics costs. Cikarang Dry Port (CDP) emerged as a breakthrough to overcome this problem. However, up to four years of operation, the utilization level of CDP is still low (less than 1% of containers flow at Tanjung Priok Port). This study aimed to analyze the factors that affect the use of CDP then model the probability of its use based on the perception of freight forwarders. To answer this question, this study use a mixed-method which combine the quantitative and qualitative methods. Based on the results of crosstabs analysis, the variables that affect the use of the CDP include the distance to CDP, warehouse ownership around CDP, CDP and service time. While based on a binary logit model, the variables that significantly affect the probability of the use of the CDP include dwelling time difference (X1), the difference in total cost (X2), and the difference CDP handling process (X3). The probability model logit is: UCDP - UTP = exp (-1,1220 - 1,246 X1 - 0,000001586 X2 - 0,396 X3) Based on the result of this study, it can be concluded that the main factor that affect the use of Cikarang Dry Port is the handling time at CDP which faster and more certain. Other factors that affect the handling cost and location of CDP.